Assessment of two methods to determine the relative contributions of the aerobic and anaerobic energy systems in racehorses - Bond, S. L.; Greco-Otto, P.; Sides, R.; Kwong, G. P.; Leguillette, R.; Bayly, W. M. (Journal of Applied Physiology, 2019)
A prospective, randomized, controlled study was designed to determine relative aerobic and anaerobic (lactic and alactic) contributions at supramaximal exercise intensities using two different methods. Thoroughbred racehorses (n = 5) performed a maximal rate of oxygen consumption (Vo2max) test and three supramaximal treadmill runs (105, 115, and 125% Vo2max). Blood lactate concentration (BL) was measured at rest, every 15 s during runs, and 2, 5, 10, 20, 30, 40, 50, and 60 min postexercise. In method 1, oxygen demand was calculated for each supramaximal intensity based on the Vo2max test, and relative aerobic and anaerobic contributions were calculated from measured Vo2 and the accumulated oxygen deficit. In method 2, aerobic contribution was calculated using the trapezoidal method to determine Vo2 during exercise. A monoexponential model was fitted to the postexercise Vo2 curve. Alactic contribution was calculated using the coefficients of this model. Lactate anaerobic contribution was calculated by multiplying the peak to resting change in BL by 3. Linear mixed-effects models were used to examine the effects of exercise intensity and method (as fixed effects) on measured outcomes (P <= 0.05). Relative aerobic and anaerobic contributions were not different between methods (P = 0.20). Horses' mean contributions were 81.4, 77.6, and 72.5% (aerobic), and 18.5, 22.3, and 27.4% (anaerobic) at 105, 115, and 125% Vo2max, respectively. Individual alactic anaerobic energy was not different between supramaximal exercise intensities (P = 0.43) and was negligible, contributing a mean of 0.11% of the total energy. Relative energy contributions can be calculated using measured Vo2 and BL in situations where the exercise intensity is unknown. Understanding relative metabolic demands could help develop tailored training programs. NEW & NOTEWORTHY Relative energy contributions of horses can be calculated using measured Vo2 and BL in situations where the exercise intensity is unknown. Horses' mean contributions were 81.4, 77.6, and 72.5% (aerobic), and 18.5, 22.3, and 27.4% (anaerobic) at 105, 115, and 125% of Vo2max, respectively. Individual alactic capacity was unaltered between supramaximal exercise intensities and accounted for a mean contribution of 0.11% of energy use.